Narratives of religious philosophy in the massagala tradition of the to bentong community of barru south sulawesi - Muhammad Suryadi R (Balai Diklat Keagamaan Ambon, 2024)
This research aims to reveal the relationship created between society, culture, and religion in the life of the To Bentong community. This research also clarifies the growing understanding that generalizes To Bentong and To Balo as different and independent cultural identities. The qualitative research model with a descriptive-study approach in this research is used to unravel narratively descriptively the interplay of culture and religion demonstrated by the To Bentong community. This research refers to two data sources. Data obtained from interview techniques as primary sources and literature, books, and journals are used as secondary sources. The collected data were then analyzed critically and carefully. The results of the study found two things. First, Massagala as a tradition of the To Bentong community directly intersects and has similarities with Islamic teachings. The substance lies in the fasting ceremony held once every three years which usually lasts a week or a month. Second, Massagala gave birth to a value system or religious philosophy that guides the To Bentong community in relations, socialization, and communication, especially with the universe.